Affective Dynamics and Ethics of AI Use among Higher Education Students: A PLS-SEM Study - Nabilah Auliah Rahman; Melda Auliyah Zakina; Aprilianti Nirmala S; Saipul Abbas (Journal of Applied Artificial Intelligence in Education, 2026)
The use of artificial intelligence (AI) in higher education is increasing rapidly, raising questions about how emotional well-being, AI credibility, and AI interaction quality shape students’ affective engagement and ethical awareness. This study employs a quantitative cross-sectional design and analyzes data using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that emotional well-being (β = 0.549, p < 0.001) and AI interaction quality (β = 0.420, p < 0.001) significantly affect affective engagement, while AI credibility has no significant effect (β = –0.045, p = 0.342). Affective engagement significantly influences ethical awareness (β = 0.597, p < 0.001) and mediates the effects of emotional well-being and interaction quality. The model explains substantial variance in affective engagement (R² = 0.561) and moderate variance in ethical awareness (R² = 0.357). These findings highlight the importance of emotional and interactional factors in fostering ethical awareness and support the need for human-centered and ethically grounded AI integration in education.